SYNERGISTICS ACTIVITY OF THE OIL EXTRACTS OF HIBISCUS SABDARIFFA - Priyam Bharathidasan, Dr. Sathish Sankar (Chelonian Research Foundation, 2023)
Introduction Tropical Hibiscus sabdariffa, also referred to as roselle or sorrel, is widely used in both traditional medicine and cooking. This plant, which is native to tropical areas, has drawn notice for possible health advantages. Meanwhile, there are serious health risks related to Enterococcus faecalis, a bacterium linked to a number of infections, including endocarditis and urinary tract infections. Aim The purpose of this study is to examine the essential oil extracted from Hibiscus sabdariffa flowers' synergistic antibacterial properties against Enterococcus faecalis. Materials and methods Hibiscus sabdariffa essential oil was extracted using the Clevenger apparatus. After thoroughly combining the plant material with distilled water, it was brought to a boil until the oil was visible. To investigate combined antibacterial effects, Abutilon indicum crude methanol extract was introduced. A comparison of the methanol extract's and its absence from the antibacterial activity revealed that the latter was more effective against Enterococcus faecalis. Results The Hibiscus sabdariffa essential oil was visible after three hours of boiling. Surprisingly, there were no antibacterial effects seen by the plant oil extract on its own. But when mixed with Abutilon indicum crude methanol extracts, a notable and significant inhibitory activity against Enterococcus faecalis was seen. Conclusion The outcomes highlight the combination of Hibiscus sabdariffa oil extract and Abutilon indicum crude methanol extract's strong inhibitory activity against Enterococcus faecalis. This cooperative approach raises the possibility of a synergistic antibacterial effect, which may have consequences for the creation of antibiotics that specifically target Enterococcus faecalis. Keywords:- Hibiscus sabdariffa oil extract, Abutilon indicum crude methanol extract, Clevenger apparatus, Universal heath, Diseases, Well being, Health, International Health policy